Kegiatan Manasik Haji dalam Pengembangan Agama dan Moral Anak Usia Dini di RA Cinta Bunda Huta Boluk Simalungun - Ahmad Syukri Sitorus; Raisah Armayantih Nasution; Aulia Ananda Putri Suhada Saragih (CV. Aksara Global Akademia, 2025)
The implementation of Hajj rituals for children is a significant practice in early childhood education, focusing on religious and moral development. This study aims to assess the impact of performing Hajj rituals on children's religious and moral growth. Using a qualitative research approach, the study describes findings from field research conducted at RA Cinta Bunda Huta Boluk Simalungun, which holds annual Hajj ritual activities for children. Data collection was done through observation and documentation. The study found that the Hajj rituals at RA Cinta Bunda are carried out through several steps: (1) Setting the departure date in alignment with the Hajj Manasik schedule, (2) notifying parents to obtain permission for their child’s participation, (3) registration with IGRA Simalungun, (4) gathering all students for the ritual, (5) reading the talbiyah, (6) receiving guidance from a supervisor upon arrival, (7) wukuf at Arafah and overnighting in Mina, (8) throwing seven small stones during stoning, (9) performing Tawaf around the Kaaba, (10) performing sa'i or jog, (11) tahallul (cutting a little hair), and (12) resting to eat dates and drink zam-zam water. The study identified seven indicators of religious and moral development resulting from these activities: (1) Recognizing the Creator and His commands, (2) Memorizing the Pillars of Islam, (3) Learning Hajj intentions, (4) Memorizing the Talbiyah reading, (5) Learning the Yemeni Rukun readings, (6) Understanding the Hajj process, and (7) Developing patience and perseverance. This study highlights the importance of religious rituals in shaping young children’s understanding of their faith and moral character.